2006
DOI: 10.1016/j.jembe.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of morphological and genetic variability in UK populations of the shore crab, Carcinus maenas Linnaeus, 1758 (Crustacea: Decapoda: Brachyura)

Abstract: Previous research has identified extensive inter-population variability in the morphology of the shore crab (Carcinus maenas L.). To determine the source of this variation (genetic or environmental), morphological and genetic data were analysed from crabs collected from eight sites around the coast of the UK. Ten morphometric traits were measured from over 800 crabs and the degree of morphological similarity among sites calculated using multivariate techniques. Allozyme electrophoresis was used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 34 publications
3
52
0
1
Order By: Relevance
“…This morphometric variability and population differentiation is in accordance with studies already carried out in the UK with this species (e.g. Brian, 2005;Brian et al, 2006). Brian et al (2006) also showed that the relationship between the phenotypic characteristics and patterns of genetic similarity was not strong.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This morphometric variability and population differentiation is in accordance with studies already carried out in the UK with this species (e.g. Brian, 2005;Brian et al, 2006). Brian et al (2006) also showed that the relationship between the phenotypic characteristics and patterns of genetic similarity was not strong.…”
Section: Discussionsupporting
confidence: 92%
“…Brian, 2005;Brian et al, 2006). Brian et al (2006) also showed that the relationship between the phenotypic characteristics and patterns of genetic similarity was not strong. The results achieved in the current study, in accordance with Brian et al (2006), suggest that genetic and phenotypic characters are in some way independent, and that environmental factors, such as habitat, wave action, predation, food supply and salinity can play an important role in the patterns of shape variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, most observed morphological traits showed a wide range of variability. This variability is an evolutionary strategy based on various genotypes (Brian et al, 2006, Henryon et al, 1989Jones et al, 2000;Lutz and Wolters, 1989) or variations of the same genotype (Ghia et al, 2006) allowing an organism to alter its morphology or behaviour (Haddaway et al, 2012). In the Czech Republic, we should consider more than only one genetic lineage; together with isolated populations from the Danube or Elbe watersheds, a special position is occupied by the stone crayfish population from Luční brook in the Giant Mountains which probably was introduced from the Balkan Peninsula (Pešek, 2013).…”
Section: Figurementioning
confidence: 99%